Youtube Media in the Listening Ability of English Education Students - Manihuruk, Leonita Maria Efipanias; Nababan, Irene Andryani (Journal of Education Technology, 2023)
This research was motivated by the learning to listen to English UHKBNP students during the Covid-19 pandemic which had not been carried out properly because students' understanding of listening skills was still lacking. The teaching and learning process during the pandemic was increasingly difficult for students to experience, resulting in disruption of the teaching and learning process. This also reduces the activeness of students in participating in listening lessons. The learning media used are also less effective, moreover the learning techniques used are still less varied. The purpose of this study was to analyze how effective the use of YouTube media was on the listening skills of UHKBNPP English students during the Covid-19 pandemic. The research method used was quasi-experimental without a control class. The steps to be carried out in this research are; 1) Do a pre test; 2) Doing treatment using Youtube media; 3) Do a post test, then conclude. Based on the t test results, there was a significant difference between the control group and the experimental group in listening ability. The experimental class that used YouTube media showed significant improvement compared to the control group. The conclusion from this study is that there is effectiveness of YouTube media in improving students' listening skills during the current Covid-19 pandemic.